Protein-based therapies for acute lung injury: targeting neutrophil extracellular traps. (June 2014) - Bosmann, Markus; Ward, Peter A
<x xml:space="preserve">Abstract</x> Introduction: Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are the acute onset of noncardiac respiratory insufficiency associated with bilateral lung infiltrations. During the past decade, mechanical ventilation strategies using low tidal volumes have reduced the mortality of ALI/ARDS to ∼ 20 – 40%. However, ALI/ARDS continues to be a major factor in global burden of diseases, with no pharmacological agents currently available. Areas covered: In this review, we discuss several inflammatory proteins involved in the molecular pathogenesis of ALI/ARDS. The complement cleavage product, C5a, is a peptide acting as a potent anaphylatoxin. C5a may trigger the formation of neutrophil extracellular traps (NETs) and release of histone proteins to the extracellular compartment during ALI/ARDS. NETs may activate platelets to release TGF-β, which is involved in tissue remodeling during the later phases of ALI/ARDS. Interception of C5a signaling or blockade of extracellular histones has recently shown promising beneficial effects in small animal models of ALI/ARDS. Expert opinion: Novel protein-based strategies for the treatment of ALI/ARDS may inspire the hopes of scientists, clinicians, and patients. Although neutralization of extracellular histones/NETs, C5a, and TGF-β is effective in experimental models of ALI/ARDS, controlled clinical trials will be necessary for further evaluation in future.